Pemberdayaan Kelompok Nelayan Pengolah Udang melalui Implementasi Integrated Fishfolk Training pada Sektor Penguatan Usaha, Sosialisasi NIB dan SPP-IRT, serta Pelatihan Keuangan di Desa Pidodo Kulon - Aji Yoga Permana Putra; Dina Novia Wulandari; Satsya Yoga Baswara; Dea Sandra Isabella; Raisya Nabila (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The Integrated Fishfolk Training program was conducted in Pidodo Kulon Village, Patebon District, Kendal Regency, which aimed at improving managerial capacity and business legality of the Shrimp Processing Fisherfolk Group. Twenty-two participants aged between 25 and 60 years took part in an intensive one-day training on August 11, 2025. The IFT approach combined financial literacy, inventory management, and business legality assistance through the Online Single Submission system (OSS). Evaluation used a scoring scale of 0–100 by pre-test and post-test assessments to measure the improvement of participants’ knowledge. Results showed that there was a significant increase in financial literacy scores from 53.64 to 75.45, and understanding business legality from 51.82 to 73.63. Also, this group got one Business Identification Number and five Home Industry Food Production Certificates for its main products: shrimp paste, shrimp chili sauce, shrimp floss, shrimp stock, and shrimp crackers. The major challenges were low digital literacy and cultural resistance toward new management methods which were well addressed by participatory approaches as well as hands-on practice respecting local wisdom. In general terms, the IFT program was effective in transforming the fisherfolk group from a traditional enterprise into a formalized micro-business unit that operates more professionally, efficiently, and sustainably.